Jute bioblanket as a soil rehabilitation strategy in Sorocaba, Brazil: Soil chemistry and SWOT approaches - da Silva, Alexandre Marco [UNESP]; Tsuchiya, Lucas Hubacek [UNESP]; Mendes, Pablo Bettio [UNESP]; de Camargo e Timo, Thiago Philipe; Cerdà, Artemio (Wiley, 2019)
Soil erosion and the invasion of exotic plant species are major constraints to achieve sustainable development around the world. Currently, we find few products devoted concomitantly to combatting soil erosion as well as the establishment of unwanted exotic plants. In this paper, we introduce a new product, called herein a bioblanket, that protects the soil and impedes the establishment of exotic plant species. This product is of simple design, and to manufacture it, we use two biodegradable materials: jute tissue and grass wastes. We designed this product to combat soil erosion and the germination and establishment of new, unwanted, invasive plant species. In this paper, we describe our evaluation of how successful this product was in terms of improving the chemical attributes of soil. We also identified the product's potentialities and weaknesses by means of strengths, weaknesses, opportunities, and threats (SWOT) analysis. The bioblanket ameliorated the chemical attributes of the soil, as evidenced especially by the neutralization of acidity (8.5%) and aluminum toxicity (33%), and by an increment in nutrients concentration. We argue that after adequate treatment and management, the residues of plants that are normally considered unwanted materials can be transformed into a raw material to control the propagation of unwanted plant species, and concomitantly control soil erosion while improving the chemical conditions of the soil. The improvement of the soil chemical attributes was one of the main positive effects reported through the SWOT analysis. In addition, the SWOT analysis revealed some features that need improvement in future generations of the product, but we argue that these features do not impede the benefits for the use of the product in its present form.
Keywords: biodegradable geotextile; controlling unwanted plant species; mulching; soil chemical dynamic; soil conservation; SWOT in environmental analysis; technological solutions for man-made slope stabilization